Analisis Peran Otoritas Jasa Keuangan (Ojk) dalam Mengawasi Pelayanan Pada Perusahaan Financial Technology (Fintech) di Indonesia - Dhea Khoirunisa; Nia Desy Arifiani; Muhammad Rizqi Maulana; Endang Kartini Panggiarti (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
With a platform that can reach the entire layer of society, it is expected to increase product sales and collaborate with business partners through electronics so that it is known as Electronic Business (E-Bussines). The innovation of the merging of financial services and information technology gave birth to new systems to run financial transaction mechanisms that help consumers called financial technology or fintech. Thus the government must provide a form of legal protection both in terms of business administrators and for the community who act as customers. One of them is the supervision and regulation of financial technology (fintech) issued by the Jasakenangan Authority (OJK). The main objective of this study is to provide knowledge on how the role of the Financial Services Authority (OJK) in overseeing services in financial technology companies (fintech) in Indonesia. This study uses a qualitative method. This article is more focused on discussing the results of previous studies related to financial technology (fintech) in Indonesia. The results of this study show that each organizer involved in the field of Financial Technology (Fintech) type of peer to peer lending must be registered and get licensing as an organizer by the OJK before starting to operate their business. In order to supervise fintech in Indonesia, OJK issued OJK Regulation No. 13/POJK.02/2018 concerning Digital Financial Innovation in the Financial Services Sector as a provision that covers the supervision and regulation of the fintech industry. This rule is intended to provide legal protection for the user of fintech service users who in the implementation of OJK's supervision use the regulatory sandbox mechanism.